Web Technology Skills Acquisition by Computer Science Students at Polytechnics In Akwa Ibom State, Nigeria - Dickson, Solomon Makasda; Idayana ALABERE; Ijeoma Peace OKECHUKWU (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
The main aim of this study was to determine the level of web technology skills acquired by computer science students in polytechnics in Akwa Ibom State-Nigeria. The study adopted a descriptive survey research method. Two research questions were raised and two research hypotheses were formulated and tested at a 0.05 significant level. Six polytechnics are made up of two public and four private polytechnics. The sample sizes consist of 343 Computer Science Students for public and private polytechnics 157 and 186 respondents’ respectively. Based on the data analyzed, the finding revealed the result of mean and standard deviation on the level of acquisition of content design skills by public and private polytechnic computer science students. However, the extent of acquisition in public Polytechnics shows six very high levels (HL) and six high levels (HL) respectively, while the results for private Polytechnics show six high levels (HL) and six low levels (LL). This implies that public Polytechnic is doing better than private Polytechnics in the acquisition of content design skills in Akwa Ibom State. It was also revealed that the result of mean and standard deviation on the level of acquisition of graphic animation skills by public and private polytechnic computer science students. However, the extent of acquisition in public Polytechnics shows one very high level (VHL) and seven high level (HL) respectively, while the results for private Polytechnics show three high-level t (HL) and five low level (LL).